IMD259: Technical Support Service and Maintenance for Information Agencies / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course is intended to provide students with the basic knowledge and skills on computer hardware and software including simple maintenance and troubleshooting in order to enhance their ICT knowledge and skills. In short, this course will bring students from the just-a-user level to the i-can-fix-this level for the computer hardware and software. In addition, students may learn on how to perform specific computing tasks such as buying a new computer, installing a new hardware and operating system and also maintaining the computer through instruction and discussion about its architecture, networking and troubleshooting